What Makes Hypertensive Patients Non-Compliant to Treatment? A Cross-Sectional Study from Peshawar (Medical Forum Monthly, 2024)
Objective: To determine the frequency of causes of non-compliance to anti-hypertensive medications.Study Design: Cross-sectional / descriptive study.Place and Duration of Study: This study was conducted at the Department of Medicine; Khyber Teaching Hospital Peshawar from January 2019 to June 2019.Materials and Methods: This study was conducted on 178non-complianthypertensive patients recruited in the study through consecutive sampling and subjected to a detailed questionnaire-based interview to determine the causes of non-compliance to treatment.Results: The mean age of the patients was 55.8 + 7.22 years. We had 53.37% males & 46.6% females in. The most common causes of treatment non-compliance identified were unaffordability (60.1%) followed by multiple drugs (39.9%), lack of information by caregiver & missed appointments (33.1% each) and occurrence of side effects (27%).Conclusion: The most common causes associated with non-compliance to hypertension treatment include unaffordability,using multiple medications at one time, lack of information given to the patients by health care providers, missed follow-up visits on part of the patients and troublesome side effects of drugs causing discontinuation of treatment.